Deaf Studies, Oral Tradition, and Old English Texts. (2nd January 2017) - Garner, Lori Ann
Abstract: Building from past work in oral theory that has productively nuanced notions of literacy and orality as multi-faceted and deeply interconnected concepts, this essay calls for an equally complex model for our understanding of the hearing experience itself, focusing in particular on Anglo-Saxon England. To this end, relevant approaches emerging from medieval studies, studies in oral tradition, and — most importantly — Deaf studies are triangulated with the goal of more fully understanding the scant and often cryptic clues that survive to us in such places as law codes, medical texts, literature, and archeological records. Scholars in Deaf studies have long applied interpretive models from oral theory to analyze the cultural expressivity of signed storytelling; the influence of Deaf studies, however, has yet to be fully felt in the fields of oral theory or Anglo-Saxon studies. Opening a dialogue across disciplines can help counteract the potential for audism inherent in "oral" tradition studies, and focusing more sharply on a specific region and period effectively complicates the history of deafness in pre-modern eras. Most importantly, close attention to Deaf studies opens awareness to categories of "hearing" and "deafness" as they were socially constructed in the early medieval world.